2020
DOI: 10.3390/su12041675
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of HPLC Pigment Analysis and Microscopy in Phytoplankton Assessment in the Seomjin River Estuary, Korea

Abstract: The distribution of microalgal species in estuaries shows marked gradients because of the mixing of marine and fresh water during tidal exchanges. To assess the spatio-temporal distribution of phytoplankton in the Seomjin River estuary (SRE), Korea, we investigated the seasonal phytoplankton communities along a salinity gradient in the estuary using both high performance liquid chromatography (HPLC) pigment analysis and light microscopy. Both types of analysis indicated that marine planktonic diatoms generally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 59 publications
0
3
1
Order By: Relevance
“…For tropical waters, Barlow et al [35] and Moreno et al [66] reported that change in the proportion of PPC is a good indicator of the response of cells to photo-oxidative damage from strong ultraviolet radiation. The low ratio in the present study was caused by high PSC values, which have mainly been reported as being associated with highly productive waters, including coastal and estuarine areas [71,72]. Although this study area is geographically an open ocean, our index results of a four-time snapshot survey imply that this region is highly productive.…”
Section: Phytoplankton Functional Groupscontrasting
confidence: 48%
“…For tropical waters, Barlow et al [35] and Moreno et al [66] reported that change in the proportion of PPC is a good indicator of the response of cells to photo-oxidative damage from strong ultraviolet radiation. The low ratio in the present study was caused by high PSC values, which have mainly been reported as being associated with highly productive waters, including coastal and estuarine areas [71,72]. Although this study area is geographically an open ocean, our index results of a four-time snapshot survey imply that this region is highly productive.…”
Section: Phytoplankton Functional Groupscontrasting
confidence: 48%
“…This may explain the high PP and Chla concentrations under very low nutrient concentrations at the high saline bay-mouth area. Higher daily irradiance and temperature may also contribute to higher primary production during summer (Montani et al, 2003;Min et al, 2012). High summer PP has also been reported in other temperate coastal bay systems .…”
Section: Low Turbidity and Factors Controlling Primary Productivitymentioning
confidence: 58%
“…Moreover, Cryptomonas spp. is dominant in many estuarine areas (Lee et al, 2020;Yoon et al, 2022). Therefore, the presence of cryptophytes in Group II was likely attributable to the low salinity due to terrestrial runoff.…”
Section: Environmental Factors and The Phytoplankton Community: Field...mentioning
confidence: 99%